Gender Bias and Disproportionate Assessment of Female Protagonists in Superhero Films: An Analysis Of Captain Marvel, Black Widow, And Black Panther: Wakanda Forever - Tobing, Sophie Grace Killa Lumban; Ali, Ahmad Juma Khatib Nur (ITScience (Information Technology and Science), 2025)
This research is a descriptive qualitative study using a content analysis approach. The problems addressed in this research are: 1. What biased judgments and attitudes are portrayed by male characters in the films Captain Marvel, Black Widow, and Black Panther 2? 2. What are the attitudes and feelings of the female superheroes in these films? This study aims to obtain factual information regarding the biased judgments and attitudes portrayed by male characters in the three films and to explore the attitudes and feelings of the female superheroes in these films. The research method used is content analysis. The results of the study indicate that female superheroes still experience biased judgments and male-dominated attitudes over women. The findings reveal that there are still male characters who believe in the ability of female characters to become leaders and to face enemy attacks with physical strength.